Analisis Kinerja Anggaran Belanja Pada Komisi Pemilihan Umum Kabupaten Sukabumi - Novsa, Siti Novsa Nurkhalisa; Darmo H Suwiryo; Evi Martaseli (AKUNTANSI 45, 2024)
Siti Novsa Nurkhalisa (1930611027) Muhaamadiyah University, Sukabumi. Analysis of Expenditure Budget Performance at the General Election Commission of Sukabumi Regency (Supervisors Dr.Darmo H Suwiryo.,S.E.,M.M and Evi Martaseli.,S.E.,M.Ak). The purpose of this research is to evaluate how well the spending budget has performed. The variables employed in this research are qualitative, and descriptive methods are used to obtain the data. These approaches include observation, interviews, and recording of the Sukabumi Regency KPU spending budget realization report.In this instance, the government carries out the obligations and responsibilities that must be met in order to produce performance that has an effective and efficient end result, and it is obvious that it must pay attention to the standard of the Sukabumi Regency General Election Commission's performance. The results of this study are that spending in the 2021-2022 LRA always shows changes in the evaluation of the spending budget, but in 2022 after entering the 2024 election stage the budget in the Sukabumi Regency KPU has a discrepancy in budget realization due to different or additional policies activities outside of planning so that they always revise the budget and the ceiling in 2022 has decreased compared to 2021 as a result of this planning. So it is hoped that in the following year it can be even better so as not to burden the financial team at the Sukabumi Regency KPU.